Using an electro-mechanical system to investigate the influence of the fatigue on the energy dissipated per cycle due to the hysteresis damping - Thinh, Van Huu; Hung, Nguyen Xuan (Vietnam Journal of Mechanics, 2004)
The energy dissipated per cycle due to the hysteresis damping is one of the criteria for determining the vibration system. The experimental results reveal that the energy dissipated per cycle increases versus the cycles to fatigue of the rotating-beam steel specimen.